Successful Reversal of the 2020 Covid-19 Response Induced Collateral Damage on Malaria Control in Saudi Arabia. (March 2022) - Fagbo, S.; Hamid, T.; Alzahrani, M.; Eldirdiry, Y.; Adam, A.; Asiri, A.
Abstract : Purpose: Saudi Arabia is committed to malaria elimination by 2025 and its National Malaria Program (NMP) has made enormous progress so far. However, in 2020, the COVID-19 pandemic response induced a collateral damage on the NMP: an unprecedented outbreak in Jazan, where malaria importation/transmission remains a challenge. Can a multisectoral, multidisciplinary response to this outbreak rapidly reverse the damage? Methods & Materials: This observational study, nested within the NMP surveillance system, analyzed indicators recorded in Jazan (Indoor Residual Spraying [IRS] coverage; confirmed patients and larval source management [LSM]) temporally for the period between 2019 to 2021. Results: By September 2021, only January to June 2021 data was available. In 2020, the COVID-19 movement restrictions and reassignment of NMP staff to pandemic response precipitated an unprecedented epidemic in Jazan with 3022 confirmed cases: comparing with 2019 figures (818), this represented a 27-fold increase. Limiting comparison to between January and June for the 3 years, patients treated were 543, 2212 and 1261, respectively. The obvious effect of the lockdown and reassigned officers is also reflected in the IRS coverage for 2019, 2020 and 2021 (till June), being 90%, 77% and 89%, respectively. The low 2020 IRS coverage (WHO minimum recommended level: 80%) supports the observed increased transmission. The 1261 cases in 2021, a 43% reduction from 2020, correlated with the 89% IRS coverage indicative of post intervention reversal. All patients were treated according to WHO protocol. Additionally, the poor indices of Anopheles arabiensis LSM (7040 for 2020, more than 2-fold increase from the 2019 figure of 3257) indicated pandemic disruption of larviciding activities. The 2021 midyear figure of 8471 suggests intensified LSM is needed to achieve further reductions in transmission. The Ministries of Health and Environment, Water and Agriculture coordinated IRS and LSM interventions. Conclusion: The pandemic response engendered an unprecedented malaria epidemic and threatened years of malaria control progress. However, the improved, post-intervention and post-lockdown data provided suggests that positive rebounds can be achieved when responses are coordinated using a multi-sectoral, One Health platform.